The life and times of Frida Kahlo [videorecording (DVD)] - Stechler, Amy, 1955-; Moreno, Rita; Downs, Lila (PBS Home Video/Paramount Home Entertainment, 2004)
Frida Kahlo was more than a great painter: her life and art reflected the maelstrom of the revolution and culture that defined the first half of the twentieth century. This film combines Kahlo's artwork with photos, archival films and interviews.